Positive electrode active material, lithium ion secondary battery, battery module, battery pack and electric device
By introducing a NASICON structural fast ion conductor layer and carbon cladding layer into lithium iron phosphate materials, the problem of low energy density of traditional lithium-ion secondary batteries is solved, and the energy density is improved and the circulation performance is maintained.
Patent Information
- Application Number
- CN202180043383.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-01-21
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-01-21
AI Technical Summary
The lithium-ion secondary batteries prepared by traditional lithium iron phosphate materials have low energy density and cannot meet the needs of some large-scale power consumption devices.
By coating the NASICON structural fast ion conductor layer and carbon cladding layer on the lithium iron phosphate matrix, the ionic conductivity and electronic conductivity of the material are improved, thereby increasing the capacity and powder compaction density.
The energy density of lithium-ion secondary batteries is improved while maintaining excellent cycling performance.
Smart Images

Figure CN115885396B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of electrochemical technology. More specifically, the present application relates to a positive electrode active material, a lithium-ion secondary battery, a battery module, a battery pack and an electric device. Background Art
[0002] With the rapid development of the new energy field, secondary batteries, especially lithium-ion secondary batteries, are widely used in various large-scale power devices, energy storage systems and various consumer products due to their excellent electrochemical properties, no memory effect and low environmental pollution.
[0003] Lithium iron phosphate is one of the most widely used cathode active materials in lithium-ion batteries. Compared with ternary cathode active materials, it has significant advantages in safety, cycle performance and cost, and is widely used in commercial vehicles, passenger cars and large-scale energy storage.
[0004] However, lithium-ion secondary batteries made from traditional lithium iron phosphate materials often have low energy density and cannot meet the needs of certain large-scale electrical devices, which puts higher requirements on the development of secondary batteries based on lithium iron phosphate.
[0005] Based on this, the present application develops a positive electrode active material with high gram capacity and high powder compaction density, and a lithium-ion secondary battery with high energy density. Summary of the invention
[0006] In view of the problems existing in the background technology, the present application provides a positive electrode active material with high gram capacity and high powder compaction density. The lithium ion secondary battery prepared from the positive electrode active material of the present application has improved energy density and excellent cycle performance while having high energy density.
[0007] One object of the present application is to provide a positive electrode active material with high gram capacity.
[0008] An object of the present application is to provide a positive electrode active material with improved powder compaction density.
[0009] One object of the present application is to provide a positive electrode sheet with improved sheet compaction density.
[0010] An object of the present application is to provide a lithium ion secondary battery with high energy density.
[0011] The inventors have discovered that one or more of the above-mentioned purposes can be achieved by adopting the technical solution of the present application.
[0012] The first aspect of the present application provides a positive electrode active material, comprising a substrate and a coating layer, wherein the coating layer covers the substrate, and the coating layer comprises a fast ion conductor layer and a carbon coating layer.
[0013] The matrix comprises one or more compounds of formula (I):
[0014] LiFe 1-a M1 a PO4 formula (I),
[0015] In the formula (I), M1 is selected from one or more of Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb and Ti, 0≤a≤0.01,
[0016] The fast ion conductor layer comprises a fast ion conductor having a NASICON structure as shown in formula (II),
[0017] Li 3-b Fe 2-b M2 b (PO4)3 Formula (II),
[0018] In the formula (II), M2 is selected from one or more of Ti, Zr, Hf, Ge and Sn with a valence of +4, and 0≤b≤1.
[0019] The positive electrode active material of the first aspect of the present application gives full play to the advantages of lithium iron phosphate in terms of low cost, high safety performance and good cycle stability, and at the same time, utilizes the coating layer (fast ion conductor layer with NASICON structure fast ion conductor and carbon coating layer) to solve the disadvantages of poor electronic conductivity and ion conductivity of lithium iron phosphate, thereby improving the gram capacity and powder compaction density of lithium iron phosphate. The lithium ion secondary battery prepared by the positive electrode active material of the first aspect of the present application has significantly improved energy density while having excellent cycle performance.
[0020] In any embodiment of the present application, optionally, in the positive electrode active material, the LiFe 1-a M1 a PO4 and the Li 3-b Fe 2-b M2 b The molar ratio of (PO4)3 is (1-x):x, and 0<x≤0.005.
[0021] In the positive electrode active material of the present application, when the molar amount x of the fast ion conductor with NASICON structure is 0<x≤0.005, the positive electrode active material has excellent gram capacity. Introducing an appropriate amount of fast ion conductor with NASICON structure into lithium iron phosphate can effectively solve the problem of poor ion conductivity, increase the gram capacity of lithium iron phosphate, and increase the energy density of the corresponding lithium ion secondary battery.
[0022] In any embodiment of the present application, optionally, the mass percentage C% of carbon in the positive electrode active material is 1% to 1.5%, and the specific surface area S of the positive electrode active material is 10 to 15 m 2 / g, and the ratio of the specific surface area S to the carbon content C% of the positive electrode active material satisfies 9≤S / C≤12.
[0023] The carbon coating layer is an important component for improving the overall electronic conductivity of the positive electrode active material of the present application.
[0024] On the one hand, the carbon coating is loose and porous, which can make the electrolyte and the lithium iron phosphate matrix fully and effectively contact, ensure the transmission of lithium ions at the interface, and improve the energy density of lithium-ion secondary batteries. On the other hand, the appropriate carbon content (1% to 1.5%) can significantly improve the conductivity of the positive electrode active electrons, thereby improving the energy density of lithium-ion secondary batteries. However, carbon is an inactive substance. When the amount of carbon coating is too much, the proportion of active substances decreases, which in turn reduces the overall gram capacity of the positive electrode active material.
[0025] The specific surface area of the positive electrode active material of the present application is mainly contributed by the loose porous carbon coating layer. The specific surface area of the positive electrode active material in the suitable range (10-15m 2 / g) helps to increase the contact area between the electrolyte and the positive electrode active material, improve the battery reaction kinetics, and is beneficial to the improvement of the battery energy density.
[0026] The ratio S / C of the carbon content and specific surface area of the positive electrode active material of the present application has a great influence on the gram capacity of the positive electrode active material and the cycle performance of the lithium ion secondary battery. When the mass percentage of carbon in the positive electrode active material and the ratio S / C of the specific surface area of the positive electrode active material are within a reasonable range under the condition that the powder compaction density is basically the same, the positive electrode active material has a high gram capacity, and the corresponding lithium ion secondary battery also has excellent cycle performance.
[0027] In any embodiment of the present application, free lithium exists in the positive electrode active material.
[0028] The free lithium in the present application is inactive free lithium that cannot be embedded in / out of the positive electrode active material. It is inevitable in the process of synthesizing lithium iron phosphate positive electrode active materials. It generally exists in the form of lithium phosphate, etc. outside the bulk structure of the lithium iron phosphate matrix, and is distinguished from the active lithium located in the bulk structure of the lithium iron phosphate matrix.
[0029] In any embodiment of the present application, optionally, the pH of the positive electrode active material is not less than 9.
[0030] The presence of the ion conductor layer of the fast ion conductor with NASICON structure accelerates the dissolution of active lithium in the bulk structure of the lithium iron phosphate matrix of the present application, so that the positive electrode active material of the present application has a higher pH value than lithium iron phosphate that is only coated with carbon but does not contain a fast ion conductor layer.
[0031] In any embodiment of the present application, optionally, there is free lithium in the positive electrode active material, and the pH of the positive electrode active material is related to the mass percentage of the free lithium N Li+ % satisfies 0.15≤pH-(36N Li+ +8)≤1.1.
[0032] Although the mechanism is not clear, after a lot of experiments and research, the inventors found that pH-(36N Li+ +8) is positively correlated with the dissolution of active lithium in the lithium iron phosphate matrix phase structure. The larger its value, the stronger the transmission ability of active lithium in the lithium iron phosphate matrix phase structure with the surrounding solution, that is, the better the lithium ion transmission performance at the interface between the positive electrode active material and the electrolyte of the present application. This shows that the introduction of NASICON type fast ion conductor makes the active lithium in the lithium iron phosphate matrix phase structure easier to dissolve. When pH-(36N Li+ +8) is within a reasonable range, the corresponding positive electrode active material has excellent gram capacity and excellent cycle performance.
[0033] In any embodiment of the present application, optionally, the volume average particle size of the positive electrode active material satisfies 1 μm≤Dv50≤2 μm, 0.4 μm≤Dv10≤0.7 μm.
[0034] When the volume average particle size of the positive electrode active material satisfies 1μm≤Dv50≤2μm, 0.4μm≤Dv10≤0.7μm, the overall particle size distribution of the positive electrode active material is reasonable, which is conducive to improving the powder compaction density of the positive electrode active material of the present application, and is conducive to improving the pole piece compaction density of the positive electrode pole piece, thereby improving the energy density of the lithium-ion secondary battery. The powder compaction density of the positive electrode active material of the present application is related to the particle size distribution of the positive electrode active material and the particle size of the primary particles. Reasonable particle size distribution of the positive electrode active material and larger primary particle size are conducive to improving the powder compaction density of the positive electrode active material.
[0035] In any embodiment of the present application, optionally, the positive electrode active material is a primary particle or a quasi-single crystal.
[0036] Increasing the particle size of the primary particles of the positive electrode active material is another way to increase the compaction density of the powder of the positive electrode active material. Under the condition of similar particle size distribution, the larger the primary particle size of the positive electrode active material, the greater the compaction density of the powder, which is conducive to improving the energy density of the corresponding lithium-ion secondary battery.
[0037] In any embodiment of the present application, optionally, the powder compaction density of the positive electrode active material ρ≥2.5g / cm 3 .
[0038] The powder compaction density of the positive electrode active material is high, the positive electrode sheet prepared therefrom has a high compaction density, and the corresponding lithium-ion secondary battery has a high energy density.
[0039] In any embodiment of the present application, optionally, the powder resistivity R of the positive electrode active material is ≤11Ω·cm.
[0040] The positive electrode active material of the present application has a significantly lower powder resistivity compared to lithium iron phosphate not coated with carbon, indicating that the provision of a carbon coating layer can significantly reduce the resistance of the positive electrode active material.
[0041] A second aspect of the present application provides a lithium-ion secondary battery, comprising the positive electrode material of the first aspect of the present application.
[0042] The lithium-ion secondary battery provided in the second aspect of the present application has improved energy density because it includes a positive electrode active material with improved gram capacity and improved powder compaction density.
[0043] In any embodiment of the present application, optionally, the lithium ion secondary battery is a button battery, and in the 0.1C charge and discharge curve of the button battery, at 2.5-2.9Vvs Li + There is a charge-discharge platform within the voltage range, which can prove the presence of NASICON fast ion conductors in the positive electrode active material of the present application.
[0044] A third aspect of the present application provides a battery module, comprising the lithium-ion secondary battery of the second aspect of the present application.
[0045] A fourth aspect of the present application provides a battery pack comprising one or more of the lithium-ion secondary battery of the second aspect of the present application or the battery module of the third aspect of the present application.
[0046] The fifth aspect of the present application provides an electrical device, comprising one or more of the lithium-ion secondary battery of the second aspect of the present application, the battery module of the third aspect of the present application, or the battery pack of the fourth aspect of the present application; the lithium-ion secondary battery or battery module or battery pack can be used as a power source for the electrical device or an energy storage unit for the electrical device.
[0047] The present application provides a positive electrode active material, which synthesizes a positive electrode active material having a fast ion conductor layer and a carbon coating layer of a NASICON structure by modifying lithium iron phosphate, and further improves the ionic conductivity and electronic conductivity of lithium ions at the interface by regulating carbon content, specific surface area, limiting the relationship between specific surface area and carbon content, pH, free lithium content, and limiting the relationship between pH and free lithium content, thereby improving the gram capacity of lithium iron phosphate. The present application also obtains a positive electrode active material with high powder compaction density and high pole sheet compaction by improving the particle size distribution of primary particles and increasing the particle size of primary particles of lithium iron phosphate, so that the lithium ion secondary battery prepared from the positive electrode active material has improved energy density and excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is a schematic structural diagram of a positive electrode active material according to one embodiment of the present application.
[0049] Figure 2 It is a schematic diagram of the effect of different primary particle sizes on powder compaction according to one embodiment of the present application.
[0050] Figure 3 It is a 0.1C charge and discharge curve diagram of the button cell corresponding to the positive electrode active materials of Example 1 and Comparative Example 1 of the present application.
[0051] Figure 4 The button cell corresponding to the positive electrode active material of Example 1 and Comparative Example 1 of the present application is 2.5-2.9VvLi + Charge and discharge curves for voltage range.
[0052] Figure 5 It is a schematic diagram of a lithium ion secondary battery according to one embodiment of the present application.
[0053] Figure 6 yes Figure 5 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0054] Figure 7 is a schematic diagram of a battery module according to an embodiment of the present application.
[0055] Figure 8 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0056] Fig. 9 yes Figure 8 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0057] Fig.10 It is a schematic diagram of an electrical device according to one embodiment of the present application.
[0058] Description of reference numerals:
[0059] 1 Battery Pack
[0060] 2 upper box
[0061] 3 lower box
[0062] 4 Battery Module
[0063] 5 Secondary batteries
[0064] 51 Housing
[0065] 52 Electrode assembly
[0066] 53 Top cover assembly DETAILED DESCRIPTION
[0067] Below, the embodiments of the positive electrode active material and its preparation method, positive electrode sheet, negative electrode sheet, secondary battery, battery module, battery pack and electric device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0068] For simplicity, the present application specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value itself can be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0069] Lithium iron phosphate is the most widely used positive electrode active material in lithium-ion batteries. Compared with ternary materials, it has significant advantages in safety, cycle performance and cost, and is widely used in commercial vehicles, passenger cars and large-scale energy storage. However, lithium-ion secondary batteries made from traditional lithium iron phosphate often have a low energy density and cannot meet the needs of some large-scale power devices, which puts higher requirements on the development of lithium-ion secondary batteries based on lithium iron phosphate.
[0070] The reasons why lithium-ion secondary batteries made of lithium iron phosphate have lower energy density are as follows:
[0071] First, lithium iron phosphate has poor electronic and ionic conductivity, which limits its gram capacity. Compared with ternary materials, lithium iron phosphate has poor ionic conductivity and its electronic conductivity is about 10 -9 S / cm, which is five orders of magnitude lower than that of ternary materials with two-dimensional diffusion channels.
[0072] Secondly, nano-sized lithium iron phosphate makes the pole piece compaction density low. In order to solve the problem of poor electronic and ionic conductivity of lithium iron phosphate, it is currently alleviated by nano-sized lithium iron phosphate. However, nano-sized lithium iron phosphate determines its lower spatial density, which in turn leads to low compaction of powder and pole piece, and ultimately leads to low volume energy density of secondary batteries. Especially in the case of thick coating, the pole piece compaction density is usually 2.4g / cm 3 . Based on the above-mentioned problems, the inventors of the present application, after a lot of research and experiments, modified lithium iron phosphate to synthesize a positive electrode active material with both a fast ion conductor layer and a carbon coating layer of a NASICON structure, and further improved the ionic conductivity and electronic conductivity of lithium ions at the phase interface by regulating the carbon content, specific surface area, limiting the relationship between specific surface area and carbon content, pH, free lithium content, and limiting the relationship between pH and free lithium content, thereby increasing the gram capacity of lithium iron phosphate. The present application also improves the particle size distribution of primary particles and increases the particle size of primary particles of lithium iron phosphate to obtain a positive electrode active material with high powder compaction density and high electrode sheet compaction, thereby increasing the energy density of lithium-ion secondary batteries.
[0073] [Positive electrode active material]
[0074] The positive electrode active material of the present application comprises a substrate and a coating layer, wherein the coating layer covers the substrate, and the coating layer comprises a fast ion conductor layer and a carbon coating layer.
[0075] The matrix comprises one or more compounds of formula (I):
[0076] LiFe 1-a M1 a PO4 formula (I),
[0077] In the formula (I), M1 is selected from one or more of Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb and Ti, 0≤a≤0.01,
[0078] The fast ion conductor layer comprises a fast ion conductor having a NASICON structure as shown in formula (II),
[0079] Li 3-b Fe 2-b M2 b (PO4)3 Formula (II),
[0080] In the formula (II), M2 is selected from one or more of Ti, Zr, Hf, Ge and Sn with a valence of +4, and 0≤b≤1.
[0081] For lithium-ion secondary batteries, the positive electrode active material is the raw material that provides lithium ions. The properties of the material itself and the properties of the interface between the material and the electrolyte directly affect the extraction and embedding of lithium ions, and thus affect the energy density of the lithium-ion secondary battery.
[0082] Lithium iron phosphate is a positive electrode active material for lithium-ion secondary batteries with high safety performance, good structural stability and low cost, but its biggest drawback is that the corresponding lithium-ion secondary battery has low energy density, which is significantly lower than that of ternary materials. In view of this drawback, this application modifies lithium iron phosphate to develop and design a positive electrode active material with high gram capacity and high powder compaction density, and the lithium-ion secondary battery prepared therefrom has significantly improved energy density.
[0083] Reference Figure 1 The positive electrode active material of the present application is a coating structure in which a coating layer coats a substrate, and the coating layer coats the substrate.
[0084] The substrate includes LiFe 1-a M1 a PO4, optionally, M1 is selected from one or more of Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb and Ti, optionally, 0≤a≤0.01. The matrix is LiFe 1-a M1 a PO4, such as LiFePO4, can fully utilize the advantages of lithium iron phosphate over ternary materials, improve the safety and structural properties of lithium-ion secondary batteries prepared therefrom, and reduce the synthesis cost of lithium-ion secondary batteries.
[0085] The coating layer is provided to compensate for the poor ionic conductivity and electronic conductivity of lithium iron phosphate, and can significantly improve the ionic conductivity and electronic conductivity of lithium iron phosphate, thereby increasing the gram capacity of lithium iron phosphate, and further increasing the energy density of the corresponding lithium-ion secondary battery.
[0086] The coating layer includes a fast ion conductor layer. Specifically, the provision of the fast ion conductor layer enables the positive electrode active material of the present application to have the following advantages:
[0087] The introduction of the fast ion conductor layer can increase the transmission rate of lithium ions during multiple lithium extraction / insertion at the positive terminal.
[0088] The fast ion conductor layer includes a fast ion conductor Li having a NASICON structure 3-b Fe 2-b M2 b (PO4)3, optionally, M2 is selected from one or more of Ti, Zr, Hf, Ge and Sn with a valence of +4, optionally, 0≤b≤1. Fast ion conductor Li with NASICON structure 3-b Fe 2-b M2 b (PO4)3 is a material with ultrafast ion conduction capability, rich three-dimensional lithium ion diffusion and transmission channels, and has the advantages of high ion conduction efficiency and strong structural stability during multiple lithium de- / insertion processes. Therefore, coating a fast ion conductor layer containing a NASICON structure fast ion conductor on the surface of the lithium iron phosphate matrix can significantly increase the transmission rate of lithium ions in multiple lithium de- / insertion at the positive terminal, improve the ion conductivity of the positive electrode active material, and then increase the gram capacity, and further, improve the energy density of the corresponding lithium ion secondary battery.
[0089] Optionally, the fast ion conductor with NASICON structure may be Li2FeTi(PO4)3, Li2FeZr(PO4)3, Li2FeSn(PO4)3, or a combination of any two or three of the above.
[0090] The coating layer also includes a carbon coating layer. Optionally, the carbon coating layer can be made of an organic carbon source, such as glucose, polyethylene glycol, etc., and coated on the surface of the fast ion conductor layer through a carbonization process. The carbon coating layer can partially coat the fast ion conductor layer, or it can completely coat the fast ion conductor layer. The provision of the carbon coating layer can significantly improve the electronic conductivity of lithium iron phosphate, make up for the defect of poor electronic conductivity of lithium iron phosphate, and improve the energy density of lithium ion secondary batteries.
[0091] Specifically, the provision of the carbon coating layer enables the positive electrode active material of the present application to have the following advantages:
[0092] The carbon coating layer in the positive electrode active material of the present application provides a suitable channel for the transmission of electrons, which can significantly increase the conduction rate of electrons in multiple lithium extraction / insertion processes, improve the electronic conductivity of lithium iron phosphate, and increase the energy density of the corresponding lithium-ion secondary battery.
[0093] The carbon coating layer of the positive electrode active material of the present application is loose and porous, which enables the electrolyte to fully and effectively contact the lithium iron phosphate matrix, thereby increasing the transmission rate of lithium ions at the interface and improving the energy density of the lithium ion secondary battery.
[0094] Coating a carbon coating on the surface of the lithium iron phosphate matrix can also improve the structural stability of the positive electrode active material, effectively prevent the iron dissolution of the positive electrode active material during long-term storage and cyclic use of the lithium-ion secondary battery, thereby ensuring the cycle life of the lithium-ion secondary battery.
[0095] The positive electrode active material of the present application uses lithium iron phosphate as the base material, giving full play to the advantages of lithium iron phosphate, such as low cost, high safety performance and good cycle stability, while using the coating layer (fast ion conductor layer and carbon coating layer) to solve the disadvantages of poor electronic conductivity and ion conductivity. The lithium ion secondary battery prepared by the positive electrode active material of the present application has significantly improved energy density while having excellent cycle performance.
[0096] In some embodiments, optionally, in the positive electrode active material, the LiFe 1-a M1 a PO4 and the Li 3-b Fe 2-b M2 b The molar ratio of (PO4)3 is (1-x):x, and 0<x≤0.005.
[0097] After a lot of experiments and research, the inventors found that in the positive electrode active material of the present application, the molar amount x of the fast ion conductor with NASICON structure has a great influence on the gram capacity of the positive electrode active material. Introducing an appropriate amount of fast ion conductor with NASICON structure into lithium iron phosphate can effectively solve the problem of poor ion conductivity, increase the gram capacity of lithium iron phosphate, and increase the energy density of the corresponding lithium ion secondary battery. The theoretical gram capacity of the fast ion conductor itself is not high, and further increasing its content within a suitable range cannot further improve the gram capacity.
[0098] Optionally, x may be 0.001, 0.002, 0.003, 0.005, or a value within a range obtained by combining any two of the above values.
[0099] In some embodiments, optionally, the mass percentage C% of carbon in the positive electrode active material is 1% to 1.5%, and the specific surface area S of the positive electrode active material is 10 to 15 m 2 / g, and the ratio of the specific surface area S of the positive electrode active material to the mass percentage content C% of carbon satisfies 9≤S / C≤12.
[0100] The carbon coating layer is an important component for improving the overall electronic conductivity of the positive electrode active material of the present application.
[0101] On the one hand, the carbon coating is loose and porous, which can make the electrolyte and the lithium iron phosphate matrix fully and effectively contact, ensure the transmission of lithium ions at the interface, and improve the energy density of lithium-ion secondary batteries. On the other hand, the appropriate carbon content (1% to 1.5%) can significantly improve the conductivity of the positive electrode active electrons, thereby improving the energy density of lithium-ion secondary batteries. However, carbon is an inactive substance. When the amount of carbon coating is too much, the proportion of active substances decreases, which in turn reduces the overall gram capacity of the positive electrode active material.
[0102] The specific surface area of the positive electrode active material of the present application is mainly contributed by the loose porous carbon coating layer. The specific surface area of the positive electrode active material in the suitable range (10-15m 2 / g) helps to increase the contact area between the electrolyte and the positive electrode active material, improve the battery reaction kinetics, and is beneficial to the improvement of the battery energy density.
[0103] However, a large specific surface area of the positive electrode active material will affect the processing performance of the slurry prepared from it, such as difficulty in increasing the solid content of the slurry and easy cracking during coating. In addition, a large specific surface area of the positive electrode active material will also cause the positive electrode active material to absorb a large amount of water, resulting in a large amount of residual water in the electrode under the same baking conditions, which will ultimately affect the cycle performance of the lithium-ion secondary battery.
[0104] When the specific surface area of the positive electrode activity is too small, it means that the specific surface contribution of the carbon coating is too small, which means that the carbon coating is not loose and porous enough, so it is not conducive to the escape / embedding of lithium ions, thereby affecting the energy density and cycle performance of the battery.
[0105] From the above discussion, it can be seen that the carbon content C% in the positive electrode active material affects the specific surface S of the positive electrode active material. The change in the specific surface S of the positive electrode active material is mainly affected by the carbon content. Both parameters affect the gram capacity of the positive electrode active material and the cycle performance of the lithium-ion secondary battery. After a lot of experiments and research, the inventors found that the ratio S / C of the carbon content and specific surface area of the positive electrode active material of the present application has a greater impact on the gram capacity of the positive electrode active material and the cycle performance of the lithium-ion secondary battery.
[0106] Although the detailed mechanism is not clear, from a physical point of view, the ratio S / C of the carbon content and the specific surface area of the positive electrode active material can be interpreted as the specific surface area of the positive electrode active material under unit carbon content. The size of this ratio can reflect the looseness of the carbon coating layer of the positive electrode active material of the present application on the one hand, and on the other hand, it can reflect the coating integrity of the carbon coating layer in the positive electrode active material. Specifically, when the compaction density of the powder is basically the same, the larger the ratio S / C of the mass percentage of carbon in the positive electrode active material and the specific surface area of the positive electrode active material, the higher the gram capacity, and the greater the energy density of the corresponding lithium-ion secondary battery. However, when the ratio S / C of the mass percentage of carbon in the positive electrode active material and the specific surface area of the positive electrode active material is too large, the cycle life of the corresponding lithium-ion secondary battery will be affected.
[0107] Optionally, the ratio S / C of the carbon content to the specific surface area of the positive electrode active material may be 9.53, 10.15, 11.67, or a value within a range obtained by combining any two of the above values.
[0108] In some embodiments, optionally, free lithium exists in the positive electrode active material.
[0109] In some embodiments, optionally, the pH of the positive electrode active material is not less than 9.
[0110] The free lithium in the present application is inactive free lithium that cannot be embedded in / out of the positive electrode active material. It is inevitable in the process of synthesizing lithium iron phosphate positive electrode active materials. It generally exists in the form of lithium phosphate, etc. outside the bulk structure of the lithium iron phosphate matrix, and is distinguished from the active lithium located in the bulk structure of the lithium iron phosphate matrix.
[0111] The presence of the ion conductor layer of the fast ion conductor with NASICON structure accelerates the dissolution of active lithium in the bulk structure of the lithium iron phosphate matrix of the present application, so that the positive electrode active material of the present application has a higher pH value than lithium iron phosphate that is only coated with carbon but does not contain a fast ion conductor layer.
[0112] In some embodiments, optionally, there is free lithium in the positive electrode active material, and the pH of the positive electrode active material is related to the mass percentage of the free lithium NLi + % satisfies 0.15≤pH-(36N Li+ The pH is the pH value of the positive electrode active material.
[0113] Although the mechanism is not clear, after a lot of experiments and research, the inventors found that pH-(36N Li++8) is positively correlated with the dissolution of active lithium in the lithium iron phosphate matrix phase structure. The larger its value, the stronger the transmission ability of active lithium in the lithium iron phosphate matrix phase structure with the surrounding solution, that is, the better the lithium ion transmission performance at the interface between the positive electrode active material and the electrolyte of the present application. This shows that the introduction of NASICON type fast ion conductor makes the active lithium in the lithium iron phosphate matrix phase structure easier to dissolve. When pH-(36N Li+ +8) is within a reasonable range (0.15≤pH-(36N Li+ +8)≤1.1), the corresponding positive electrode active material has excellent gram capacity and excellent cycle performance.
[0114] Specifically, the test process of the free lithium content in the positive electrode active material of the present application is as follows: 30g of the positive electrode active material is added to 100mL of water, stirred for 30min and filtered, 25mL of the filtrate is added dropwise with 0.1mol / L dilute hydrochloric acid, and the curve of the change of the filtrate pH with the amount of dilute acid added is recorded. The curve will have a mutation point in the range of filtrate pH 4 to 5.5, and the volume V of dilute hydrochloric acid added at the mutation point is recorded. The free lithium content in the positive electrode active material can be calculated by the following formula: N Li+ % = C × V × 4 × 6.941 / 30 × 100%.
[0115] Although the mechanism is not clear, the inventors have found through a lot of experiments and research that: pH-(36N Li+ +8) can reflect the positive effect of the introduction of NASICON fast ion conductors on promoting the dissolution of active lithium in the positive electrode active material in physical sense, pH-(36N Li+ +8) has a significant impact on the gram capacity and cycle performance of the corresponding lithium-ion secondary battery.
[0116] Specifically, pH-(36N Li+ +8) is positively correlated with the dissolution of active lithium in the bulk structure. The larger its value, the stronger the transport capacity of active lithium in the bulk structure of the positive electrode active material and the surrounding solution, that is, the better the transport performance of lithium ions at the interface, indicating that the introduction of NASICON fast ion conductors makes it easier for active lithium in the bulk structure of the positive electrode active material to dissolve. However, when pH-(36N Li+ +8) is too large, indicating that too much active lithium is dissolved in the bulk structure of the positive electrode active material, which indirectly reflects that the structural stability of the lithium iron phosphate matrix used to provide active lithium is poor, thereby affecting the cycle performance of the corresponding lithium-ion secondary battery.
[0117] Secondly, pH-(36N Li++8) can also reflect the coating integrity of the carbon coating layer. When the content of NASICON fast ion conductor remains unchanged, pH-(36N Li+ When the pH-(36N+8) value is large (more than 1.1), it indicates that the carbon coating is poor, which in turn affects the cycle performance of the lithium-ion secondary battery. Li+ +8) value is small (lower than 0.15), the S / C value is small, indicating that the carbon coating is denser, indicating that the coating integrity of the carbon coating layer is better.
[0118] Optionally, pH-(36N Li+ +8) can be 0.18, 0.41, 0.53, 1.04, 1.06, or a range obtained by combining any two of the above values.
[0119] In some embodiments, optionally, the volume average particle size of the positive electrode active material satisfies 1 μm≤Dv50≤2 μm, 0.4 μm≤Dv10≤0.7 μm.
[0120] In the present application, Dv10 is the particle size (unit: μm) corresponding to the cumulative volume distribution percentage of the positive electrode active material reaching 10%; Dv50 is the particle size (unit: μm) corresponding to the cumulative volume distribution percentage of the positive electrode active material reaching 50%. After a lot of research and experiments, the inventors found that when the volume average particle size of the positive electrode active material satisfies 1μm≤Dv50≤2μm, 0.4μm≤Dv10≤0.7μm, the overall particle size distribution of the positive electrode active material is reasonable, which is beneficial to improve the powder compaction density of the positive electrode active material of the present application, and is beneficial to improve the pole piece compaction density of the positive electrode sheet, thereby improving the energy density of the lithium-ion secondary battery. The powder compaction density of the positive electrode active material of the present application is related to the particle size distribution of the positive electrode active material and the particle size of the primary particles. Reasonable particle size distribution of the positive electrode active material and larger primary particle size are conducive to improving the compaction density of the positive electrode active material powder.
[0121] Specifically, when the Dv50 of the positive electrode active material is large (exceeding 2 μm), or when the Dv10 is lower than 0.4 μm or higher than 0.7 μm, the particle size distribution of the positive electrode active material is unreasonable, thereby reducing the powder compaction density of the positive electrode active material and further reducing the compaction density of the electrode sheet.
[0122] Optionally, Dv50 may be 1.2, 1.3, 1.4, 1.6, 1.7, 1.8, or a value within a range obtained by combining any two of the above values.
[0123] Optionally, Dv10 may be 0.43, 0.47, 0.49, 0.51, 0.52, 0.54, 0.55, 0.56, 0.58, 0.61, or a value within a range obtained by combining any two of the above values.
[0124] In some embodiments, optionally, the positive electrode active material is a primary particle or a quasi-single crystal.
[0125] Increasing the particle size of the primary particles of the positive electrode active material is another way to increase the compaction density of the powder of the positive electrode active material. Under similar particle size distribution conditions, the larger the primary particle size of the positive electrode active material, the greater the compaction density of the powder. Figure 2 As shown, Figure 2 (a) and Figure 2 The black discs in (b) represent primary particles. Figure 2 (a) and Figure 2 The particle size distribution of the positive electrode active material as a whole is similar in (b), but Figure 2 The primary particle size in (a) is large, so the powder compaction density is higher ( Figure 2 (b) has many gaps).
[0126] Compared with lithium iron phosphate coated only with carbon, the positive electrode active material of the present application is a primary particle or a quasi-single crystal, and its primary particle size is larger, so it has improved powder compaction density and pole piece compaction density, which is beneficial to improve the energy density of the corresponding lithium-ion secondary battery.
[0127] In some embodiments, optionally, the powder compaction density of the positive electrode active material is ρ≥2.5g / cm 3 .
[0128] The positive electrode active material has a high powder compaction density, the positive electrode sheet prepared therefrom has a high compaction density, and the corresponding lithium-ion secondary battery has a high energy density. Optionally, the powder compaction density ρ value of the positive electrode active material can be 2.53, 2.54, 2.55, 2.56, 2.57, 2.59, or a value within the range obtained by combining any two of the above values.
[0129] In some embodiments, optionally, the powder resistivity R of the positive electrode active material is less than or equal to 11 Ω·cm.
[0130] The positive electrode active material of the present application has a significantly lower powder resistivity than lithium iron phosphate without carbon coating (whose resistivity exceeds 2E5), indicating that the provision of the carbon coating layer can significantly reduce the resistance of the positive electrode active material. However, when the powder resistivity R of the positive electrode active material exceeds 11Ω·cm, for example, when R is 18.7Ω·cm, the gram capacity of the positive electrode active material is reduced.
[0131] Optionally, the powder resistivity R of the positive electrode active material may be 3.5, 4.3, 2.7, 8.7, 9.8, or a value within a range obtained by combining any two of the above values.
[0132] In one embodiment of the present application, a lithium ion secondary battery is provided.
[0133] Generally, lithium-ion secondary batteries include a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0134] [Positive electrode]
[0135] The present application provides a positive electrode plate, comprising the positive electrode active material described in the present application.
[0136] The positive electrode plate of the present application includes a positive electrode active material having a NASICON fast ion conductor layer and a carbon coating layer, and has excellent plate compaction density and gram capacity, which is beneficial to improving the energy density of the lithium-ion secondary battery.
[0137] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0138] In some embodiments, reference Figure 3 and Figure 4 , a button cell prepared with the positive electrode active material of the first aspect of the present application, wherein in the 0.1C charge-discharge curve of the button cell, at 2.5-2.9Vvs Li + There is a charge-discharge platform within the voltage range, which can prove the presence of NASICON fast ion conductors in the positive electrode active material of the present application.
[0139] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0140] In the lithium-ion secondary battery of the present application, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0141] The positive electrode film layer may also optionally include a conductive agent. However, there is no specific limitation on the type of the conductive agent, and those skilled in the art may select it according to actual needs. As an example, the conductive agent used for the positive electrode film layer may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0142] In the present application, the positive electrode sheet can be prepared according to methods known in the art. As an example, the positive electrode active material, conductive agent and binder of the present application can be dispersed in a solvent (such as N-methylpyrrolidone (NMP)) to form a uniform positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet is obtained.
[0143] [Negative electrode]
[0144] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0145] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0146] In the lithium-ion secondary battery of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material matrix. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material matrix (such as a matrix of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0147] In the lithium-ion secondary battery of the present application, the negative electrode film layer generally comprises a negative electrode active material and an optional binder, an optional conductive agent and other optional auxiliary agents, and is generally formed by coating and drying a negative electrode slurry. The negative electrode slurry coating is generally formed by dispersing the negative electrode active material and the optional conductive agent and binder in a solvent and stirring them uniformly. The solvent may be N-methylpyrrolidone (NMP) or deionized water.
[0148] As an example, the conductive agent may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0149] As an example, the binder can be selected from one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0150] Other optional auxiliary agents include, for example, thickeners (such as sodium carboxymethyl cellulose (CMC-Na)).
[0151] In the lithium-ion secondary battery of the present application, the negative electrode film layer may optionally include other commonly used negative electrode active materials in addition to the negative electrode active material. For example, as other commonly used negative electrode active materials, artificial graphite, natural graphite, soft carbon, hard carbon, silicon matrix material, tin matrix material and lithium titanate etc. may be listed. The silicon matrix material may be selected from one or more of elemental silicon, silicon oxide compound, silicon carbon composite, silicon nitrogen composite and silicon alloy. The tin matrix material may be selected from one or more of elemental tin, tin oxide compound and tin alloy.
[0152] [Electrolytes]
[0153] The electrolyte plays the role of conducting ions between the positive electrode plate and the negative electrode plate. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte).
[0154] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0155] In some embodiments, the electrolyte salt can be selected from one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalatophosphate)) and LiTFOP (lithium tetrafluorooxalatophosphate).
[0156] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0157] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0158] [Isolation film]
[0159] Lithium-ion secondary batteries using electrolytes and some lithium-ion secondary batteries using solid electrolytes also include a separator. The separator is arranged between the positive electrode plate and the negative electrode plate to play an isolating role. The present application has no particular restrictions on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected. In some embodiments, the material of the separator can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular restrictions. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular restrictions.
[0160] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0161] In some embodiments, the lithium-ion secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0162] In some embodiments, the outer packaging of the lithium ion secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as plastic, polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS) can be listed.
[0163] The present application has no particular limitation on the shape of the lithium-ion secondary battery, which may be cylindrical, square, or any other shape. Figure 5 The lithium ion secondary battery 5 is a square structure as an example.
[0164] In some embodiments, reference Figure 6 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0165] [Battery module]
[0166] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0167] Figure 7 4 is an example of a battery module. Figure 7 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0168] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0169] [Battery Pack]
[0170] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0171] Figure 8 and Fig. 9 1 is a battery pack 1 as an example. Figure 8 and Fig. 9 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0172] [Electrical devices]
[0173] In addition, the present application also provides an electrical device, the device comprising one or more of the lithium-ion secondary battery, battery module, or battery pack provided in the present application. The lithium-ion secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0174] As the electrical device, a lithium-ion secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0175] Fig.10 The power consumption device is used as an example. The power consumption device may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the high power and high energy density requirements of the device for lithium-ion secondary batteries, a battery pack or a battery module may be used.
[0176] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a lithium-ion secondary battery may be used as a power source.
[0177] Example
[0178] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0179] Example 1
[0180]
Preparation of positive electrode active materials
[0181] Ferrous oxalate, lithium dihydrogen phosphate and titanium oxide are used as raw materials, and mixed according to the molar ratio of ferrous oxalate: lithium dihydrogen phosphate: titanium oxide = 1: 1.04: 0.003, and glucose and polyethylene glycol are added as carbon sources, and the added mass ratio of glucose and polyethylene glycol is 1: 1, and the carbon source accounts for 20% of the total weight of the solid raw materials. According to the mass ratio of solid raw material: water = 1: 1, deionized water is added to the solid raw material, and wet grinding is performed to obtain a ground slurry. The obtained slurry is spray dried, and then placed in a roller furnace for sintering, sintered at 780 for 24 hours, and nitrogen is introduced during the sintering process. After the sintering is completed, the material is naturally cooled to a temperature of less than 80 and then discharged to obtain a calcined material. The calcined material is crushed, screened, demagnetized, and then vacuum packaged to obtain the positive electrode active material of Example 1 of the present application.
[0182]
Preparation of positive electrode
[0183] The positive electrode active material, binder polyvinylidene fluoride (PVDF), and conductive agent acetylene black obtained above were mixed in a mass ratio of 96.5:2.0:1.5, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added and stirred to form a uniform positive electrode slurry. The slurry was coated on a 13 μm thick carbon-coated aluminum foil of the positive electrode current collector, and the coating surface density was 26 mg / cm 2 . Then it is dried, cold pressed and slit to obtain the positive electrode sheet.
[0184]
Preparation of negative electrode sheet
[0185] The negative electrode active material graphite, thickener sodium carboxymethyl cellulose, adhesive styrene butadiene rubber, and conductive agent acetylene black are mixed in a mass ratio of 97:1:1:1, and deionized water is added to obtain negative electrode slurry under the action of a vacuum mixer. The negative electrode slurry is evenly coated on a copper foil with a thickness of 8μm. Subsequently, it is dried, cold pressed, and slit to obtain a negative electrode sheet.
[0186]
Preparation of electrolyte
[0187] Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are prepared into a mixed solution in a volume ratio of 20:20:60, and then fully dried lithium salt is dissolved in the mixed solution, and then 10wt% of fluoroethylene carbonate additive is added and mixed evenly to obtain an electrolyte. The concentration of the lithium salt is 1 mol / L. The entire operation process is carried out in an argon atmosphere glove box with a water content of less than 10ppm.
[0188]
Isolation film
[0189] A polyethylene film with a thickness of 12 μm was used as the separator.
[0190] Example 2
[0191] Except for replacing titanium oxide with zirconium oxide in the [Preparation of Positive Electrode Active Material] section, the other steps of Example 2 are the same as those of Example 1.
[0192] Example 3
[0193] Except that titanium oxide is replaced by tin oxide in the [Preparation of Positive Electrode Active Material] section, the other steps of Example 3 are the same as those of Example 1.
[0194] Example 4
[0195] Except that the mass ratio of glucose and polyethylene glycol added in the [Preparation of Positive Electrode Active Material] is replaced with 7:3, the other steps of Example 4 are the same as those of Example 1.
[0196] Example 5
[0197] Except that the mass ratio of glucose and polyethylene glycol added in the [Preparation of Positive Electrode Active Material] is replaced with 3:7, the other steps of Example 4 are the same as those of Example 1.
[0198] Example 6
[0199] Except that in the [Preparation of Positive Electrode Active Material] section, the molar ratio of ferrous oxalate, lithium dihydrogen phosphate, and titanium oxide is changed to ferrous oxalate: lithium dihydrogen phosphate: titanium oxide = 1:1.04:0.002, the other steps of Example 6 are the same as those of Example 1.
[0200] Example 7
[0201] Except that in the [Preparation of Positive Electrode Active Material] section, the molar ratio of ferrous oxalate, lithium dihydrogen phosphate, and titanium oxide is changed to ferrous oxalate: lithium dihydrogen phosphate: titanium oxide = 1:1.04:0.001, the other steps of Example 7 are the same as those of Example 1.
[0202] Example 8
[0203] Except that in the [Preparation of Positive Electrode Active Material] section, the molar ratio of ferrous oxalate, lithium dihydrogen phosphate, and titanium oxide is changed to ferrous oxalate: lithium dihydrogen phosphate: titanium oxide = 1:1.04:0.01, the other steps of Example 8 are the same as those of Example 1.
[0204] Example 9
[0205] Except that in the [Preparation of Positive Electrode Active Material] section, all carbon sources are replaced with glucose, the other steps of Example 9 are the same as those of Example 1.
[0206] Example 10
[0207] Ferrous oxalate, lithium dihydrogen phosphate and titanium oxide are used as raw materials, and mixed according to the molar ratio of ferrous oxalate: lithium dihydrogen phosphate: titanium oxide = 1: 1.04: 0.003, and glucose and polyethylene glycol are added as carbon sources, and the added mass ratio of glucose and polyethylene glycol is 1: 1, and the carbon source accounts for 15% of the total weight of the solid raw materials. Deionized water is added to the solid raw materials according to the mass ratio of solid raw materials: water = 1: 1, and wet grinding is performed to obtain a ground slurry. The obtained slurry is spray-dried, and then placed in a roller furnace for sintering, sintering at 780 for 24 hours, and nitrogen is introduced during the sintering process. After the sintering is completed, the material is naturally cooled to a temperature less than 80 and then discharged to obtain a calcined material. After the calcined material is crushed, a dense carbon coating layer is deposited on the surface of the crushed calcined material by chemical vapor deposition (CVD) (the carbon source used in the CVD method is ethylene, and the ratio of the carbon source to the crushed material is 1:20), and then after screening and demagnetization, the positive electrode active material of Example 10 of the present application is obtained.
[0208] Embodiment 11
[0209] In the [Preparation of Positive Electrode Active Material] section, Example 13 increases the Dv50 and Dv10 of the positive electrode active material by placing the calcined material into a jet mill and adjusting the rotation speed of the classifying wheel. The other steps of Example 11 are the same as those of Example 1.
[0210] Example 12
[0211] Except that in the [Preparation of Positive Electrode Active Material] section, the molar ratio of ferrous oxalate, lithium dihydrogen phosphate, and titanium oxide is changed to ferrous oxalate: lithium dihydrogen phosphate: titanium oxide = 1:1.04:0.005, the other steps of Example 12 are the same as those of Example 1.
[0212] Embodiment 13
[0213] In the [Preparation of Positive Electrode Active Material] section, the sintering temperature of Example 13 is 760°C, and the other steps of Example 13 are the same as those of Example 1.
[0214] Comparative Example 1
[0215] Iron phosphate and lithium carbonate are used as raw materials, mixed in a molar ratio of iron phosphate: lithium carbonate = 1: 1.04, and glucose and polyethylene glycol are added as carbon sources, the mass ratio of glucose and polyethylene glycol is 1: 1, and the carbon source accounts for 20% of the total weight of the solid raw materials. Deionized water is added to the solid raw materials in a mass ratio of solid raw materials: water = 1: 1, and wet grinding is performed to obtain a ground slurry. The obtained slurry is spray dried, then placed in a roller furnace for sintering, sintered at 780 for 24 hours, and nitrogen is introduced during the sintering process. After the sintering is completed, the material is naturally cooled to a temperature of less than 80 and then discharged to obtain a calcined material. The calcined material is crushed, screened, demagnetized, and then vacuum packaged to obtain the positive electrode active material of Comparative Example 1 of the present application.
[0216] Comparative Example 2
[0217] Take iron phosphate and lithium carbonate as raw materials, mix them in a molar ratio of iron phosphate: lithium carbonate = 1: 1.04, add deionized water to the solid raw material in a mass ratio of solid raw material: water = 1: 1, and wet grind to obtain a ground slurry. The obtained slurry is spray dried, then placed in a roller furnace for sintering, sintered at 780 for 24 hours, and reducing hydrogen is introduced during the sintering process. After the sintering is completed, the material is naturally cooled to a temperature of less than 80 and then discharged to obtain a calcined material. The calcined material is crushed, screened, demagnetized, and then vacuum packaged to obtain the positive electrode active material of Comparative Example 2 of the present application.
[0218]
Preparation of lithium-ion secondary batteries
[0219] The positive electrode sheets, separators, and negative electrode sheets in Examples 1 to 13 and Comparative Examples 1 to 2 are stacked in order, with the separators between the positive and negative electrode sheets, and then wound into bare cells. The bare cells are welded with pole ears, and the bare cells are placed in an aluminum shell, and baked at 80°C to remove water, and then the electrolyte is injected and sealed to obtain an uncharged secondary battery. The uncharged secondary battery is then subjected to the processes of standing, hot and cold pressing, formation, shaping, and capacity testing to obtain a lithium-ion secondary battery product.
[0220]
Test of parameters related to positive electrode active materials
[0221] 1. Free lithium content N Li+ % of tests
[0222] Free lithium content N Li+% test is based on the standard GB / T 9725-2007. At room temperature, take 30g of positive electrode active material from all embodiments and all comparative examples, add them into 100mL of water, stir for 30min and filter. Take 25mL of the filtrate and add dilute hydrochloric acid with a concentration C of 0.1mol / L, and record the curve of pH change with the amount of dilute hydrochloric acid added. The curve will have a mutation point in the pH range of 4 to 5.5, and the volume V of dilute hydrochloric acid added at the mutation point is recorded. For detailed parameter settings, refer to WI-PCA-034 "Guidelines for Free Lithium Potentiometric Titration Test (Iron Lithium)". The free lithium content corresponding to all embodiments and all comparative examples is calculated by the following formula:
[0223] N Li+ % = C × V × 4 × 6.941 / 30 × 100%.
[0224] 2. pH test of positive electrode active materials
[0225] The pH test of positive electrode active materials is based on GB / T 9724-2007. At room temperature, 10g of positive electrode active materials of all embodiments and all comparative examples were taken, added to 100mL of water, stirred for 30min, and filtered after standing for 90min. The pH of the filtrate of all embodiments and all comparative examples was measured with a pH meter (model pHS-3C), which is the pH value of the positive electrode active material corresponding to each. For detailed parameter settings, refer to WI-PCA-031 "Guidelines for pH Testing of Powders and Emulsions".
[0226] 3. Powder compaction density test
[0227] Weigh 1g of positive electrode active material in all embodiments and comparative examples respectively, and add it into a cylindrical mold, the cross-sectional area of the circular hole of the mold is S. Apply 3t pressure to the powder in the mold, and maintain the pressure for 30s, and record the thickness of the powder as t. Then the powder compaction density of the positive electrode active material corresponding to all embodiments and all comparative examples can be calculated by the following formula:
[0228] ρ = m / (S×t).
[0229] 4. Pole compaction density test
[0230] The pole piece is cut into 1000mm long diaphragms, and the pole piece is rolled under a certain pressure. Due to the ductility of the aluminum foil, the length of the diaphragm is 1006mm. Then, 1540.25mm is punched on the diaphragm. 2 The weight M and thickness L of the small disc are measured. The pure aluminum foil is punched into 1540.25mm 2 The empty aluminum foil mass M0 is weighed, and the compaction density of the positive electrode sheets corresponding to all embodiments and all comparative examples can be calculated by the following formula:
[0231] PD=(M-M0) / 1.54025 / 2 / L.
[0232] 5. Carbon content test
[0233] The positive electrode active materials in all the above embodiments and comparative examples were burned in a high-frequency induction furnace and then tested for carbon content using an infrared absorption method. The specific testing process was based on the standard GB / T 20123-2006 / ISO 15350:2000.
[0234] 6. Specific surface area test
[0235] The specific surface areas of the positive electrode active materials of all the above-mentioned embodiments and comparative examples were tested by a Tristar 3020 instrument, and the specific testing process was in accordance with the standard GB / T 19587-2004.
[0236] 7. Dv10 and Dv50 tests
[0237] The Dv10 and Dv50 of the positive active materials in all the above embodiments and comparative examples were analyzed and tested using a Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd., UK, in accordance with the particle size distribution laser diffraction method of standard GB / T 19077-2016.
[0238] 8. Powder resistivity test
[0239] The powder resistivity of the positive electrode active materials of all the above embodiments and comparative examples was tested using a powder resistivity tester (ST2722) and analyzed and tested according to the standard GB / T 30835-2014.
[0240] 9. ICP test process
[0241] The element test of the positive electrode active material in all the above embodiments and comparative examples adopts inductively coupled plasma atomic emission spectrometry. For details, please refer to EPA 6010D-2014 Inductively Coupled Plasma-OpticalEmmission Spectrometry, and the test instrument uses ICP-OES.
[0242]
Battery performance test
[0243] 1. Capacity test of power consumption
[0244] The positive electrode active material of Example 1, the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black are mixed in a mass ratio of 95:5:5, and an appropriate amount of N-methylpyrrolidone (NMP) solvent is added, and the mixture is stirred thoroughly to form a uniform positive electrode slurry. The slurry is coated on an aluminum foil with a thickness of 1 μm for the positive electrode current collector, and then dried and cold pressed. Then it is punched into small discs with a diameter of 14 mm for use as positive electrode sheets. A lithium sheet is used as the negative electrode, and a 12 μm thick polypropylene isolation film and the electrolyte in the embodiment are used to assemble a button half-cell. The button half-cell is charged and discharged at rates of 0.1C and 1C, respectively, and the gram capacity at different rates is recorded.
[0245] The test process of the gram capacity of the positive electrode active material of other embodiments and comparative examples is the same as the test process of the gram capacity of the positive electrode active material of the above-mentioned embodiment 1.
[0246] 2. Cycle performance test
[0247] All lithium-ion secondary batteries of the embodiments and comparative examples were placed in a 60°C oven, left to stand for 2 hours, and then subjected to charge and discharge tests. A charge and discharge cycle process is as follows: 1C constant current charging to 3.65V, continue constant voltage charging until the charging current is less than 0.05C and then cut off; pause for 5 minutes; 1C constant current discharge to 2.5V; pause for 5 minutes. The above is a charge and discharge cycle of the battery, which is repeated continuously until the battery capacity decays to 80% of the initial value, and the number of cycles is recorded.
[0248] The positive electrode active material related parameters and battery performance test parameters of all the above examples and comparative examples are listed in Table 1 and Table 2, respectively.
[0249] Table 1: Table of parameters of positive electrode active materials of Examples and Comparative Examples
[0250]
[0251]
[0252] Table 2: Battery performance test parameters of the embodiments and comparative examples
[0253]
[0254] [Analysis of the influence of NASICON structure fast ion conductor on the gram capacity of positive electrode active materials]
[0255] Based on Table 1 and Table 2, the positive electrode active materials of Examples 1 to 13 include a fast ion conductor layer having a NASICON structure fast ion conductor, which has significantly improved gram capacity of the positive electrode active material compared to Comparative Examples 1 and 2, regardless of whether it is 0.1C discharge gram capacity or 1C discharge gram capacity.
[0256] Moreover, Examples 1 to 3 show that the fast ion conductors Li2FeTi(PO4)3, Li2FeZr(PO4)3, and Li2FeSn(PO4)3 containing different types of metal elements have significantly improved gram capacity of the positive electrode active material compared to Comparative Examples 1 and 2, whether it is 0.1C discharge gram capacity or 1C discharge gram capacity.
[0257] Compared with Examples 1 to 13, Comparative Example 1 has only a carbon coating layer but no fast ion conductor layer, and Comparative Example 2 has neither a carbon coating layer nor a fast ion conductor layer. The corresponding positive electrode active materials have significantly lower 0.1C discharge gram capacity and 1C discharge gram capacity than Examples 1 to 13.
[0258] [Analysis of the influence of the content of NASICON structure fast ion conductor on the gram capacity of positive electrode active materials]
[0259] Comprehensively comparing Table 1 and Table 2, it can be seen that when the molar amount of Li2FeTi(PO4)3 in the positive electrode active material is 0<x≤0.005 and the corresponding molar amount of LiFePO4 is 0.995≤1-x<1, compared with Example 8 (x exceeds 0.05) and Comparative Example 1 (x=0), they all have higher gram capacity of positive electrode active material. While Example 8 (x exceeds 0.05), the first charge gram capacity and 0.1C discharge gram capacity of the corresponding positive electrode active material are lower, and Comparative Example 1 (x=0) corresponds to a significantly reduced gram capacity of the positive electrode active material, whether it is 0.1C discharge gram capacity or 1C discharge gram capacity.
[0260] [Analysis of the influence of the ratio of specific surface area S to carbon mass percentage C% S / C]
[0261] From Table 1 and Table 2, and from the comparison of Examples 1, 4, 5, 9, and 10, it can be seen that when the S / C is in the range of 9 to 12, the corresponding positive electrode active materials have good 0.1C and 1C gram capacities and cycle performance of lithium ion secondary batteries. However, when the S / C exceeds 12, as shown in Example 9, the cycle performance of the lithium ion secondary battery decreases. When the S / C is less than 9, the 0.1C and 1C gram capacities of the corresponding positive electrode active materials are low.
[0262] [Analysis of the effect of pH on the gram capacity of positive electrode active materials]
[0263] Based on Table 1 and Table 2, and by comparing all the embodiments and comparative examples, in Embodiments 1 to 15, the presence of the fast ion conductor layer can accelerate the release of active lithium in the bulk structure of the lithium iron phosphate matrix, so the pH is higher than that of Comparative Example 1.
[0264]
pH-(36NLi+ +8) Impact Analysis
[0265] Comprehensive Table 1 and Table 2, comprehensive comparison of Examples 1, 4, 5, 7, 8, 9, 10 shows that when pH-(36N Li+ +8) in the range of 0.15 to 1.1, the corresponding positive electrode active materials have good 0.1C and 1C gram capacity and lithium ion secondary battery cycle performance. However, when pH-(36N Li+ When pH-(36N+8) exceeds 1.1, as shown in Example 9, the cycle performance of the corresponding lithium ion secondary battery is reduced. Li+ +8) is lower than 0.15, the 0.1C and 1C gram capacities of the corresponding positive electrode active materials are lower.
[0266] [Effect of particle size distribution of positive electrode active materials on powder compaction density]
[0267] From Table 1 and Table 2, it can be seen from the comprehensive comparison of Examples 1 to 13 that when the volume particle size of the positive electrode active material satisfies 1 μm ≤ Dv50 ≤ 2 μm, 0.4 μm ≤ Dv10 ≤ 0.7 μm, the corresponding positive electrode active material has a reasonable particle size distribution as a whole, and has a powder compaction density (ρ ≥ 2.5 g / cm 3 ). However, when Dv50 is large, such as in Example 11, it has a certain impact on the overall particle size distribution of the positive electrode active material, so the corresponding powder compaction density and pole piece compaction density of the positive electrode active material are low. Similarly, when Dv10 is lower than 0.4 μm (Example 13) or higher than 0.7 μm (Example 11), it has a certain impact on the overall particle size distribution of the corresponding positive electrode active material, so the corresponding powder compaction density and pole piece compaction density of the positive electrode active material are low.
[0268] [Effect of powder resistivity on gram capacity of positive electrode active materials]
[0269] From Table 1 and Table 2, and from the comprehensive comparison of Examples 1, 4, 5, 9, and 10, it can be seen that when the powder resistivity R of the positive electrode active material is ≤ 11Ω·cm, they all have good 0.1C and 1C gram capacities. However, when the powder resistivity R of the positive electrode active material exceeds 11Ω·cm, as in Example 13, both 0.1C and 1C gram capacities are reduced to a certain extent.
[0270] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely illustrative, and embodiments having substantially the same structure as the technical idea and exerting the same effects within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be thought of by those skilled in the art to the embodiments, and other methods of combining some of the constituent elements in the embodiments to construct are also included in the scope of the present application.
Claims
1. A positive electrode active material, characterized in that: It comprises a substrate and a coating layer, wherein the coating layer covers the substrate, and the coating layer comprises a fast ion conductor layer and a carbon coating layer, The matrix includes one or more compounds of formula (I): LiFe 1-a M1 a PO4 of formula (I), In the formula (I), M1 is selected from one or more of Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb and Ti, 0≤a≤0.01, The fast ion conductor layer comprises a NASICON structure as shown in formula (II) Fast ion conductors, Li 3-b Fe 2-b M2 b (PO4)3 formula (II), In the formula (II), M2 is selected from one or more of Ti, Zr, Hf, Ge and Sn with a valence of +4, and 0<b≤1.
2. The positive electrode active material according to claim 1, characterized in that In the positive electrode active material, the LiFe 1-a M1 a PO4 and the Li 3-b Fe 2-b M2 b The molar ratio of (PO4)3 is (1-x):x, and 0 <x≤0.005。 3. The positive electrode active material according to claim 1, characterized in that The mass percentage C% of carbon in the positive electrode active material is 1% to 1.5%, The specific surface area S of the positive electrode active material is 10-15 m 2 / g, The ratio of the specific surface area S to the carbon content C% of the positive electrode active material satisfies 9≤S / C≤12.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that The pH of the positive electrode active material is not less than 9.
5. The positive electrode active material according to any one of claims 1 to 3, characterized in that There is free lithium in the positive electrode active material, and the pH of the positive electrode active material is related to the mass percentage of the free lithium. Li+ % satisfies 0.15≤pH-(36N Li+ +8)≤1.
1.
6. The positive electrode active material according to any one of claims 1 to 3, characterized in that The volume average particle size of the positive electrode active material satisfies 1 μm≤Dv50≤2 μm and 0.4 μm≤Dv10≤0.7 μm.
7. The positive electrode active material according to claim 6, characterized in that The positive electrode active material is a primary particle or a quasi-single crystal.
8. The positive electrode active material according to any one of claims 1 to 3, characterized in that The powder compaction density of the positive electrode active material is ρ≥2.5g / cm 3 .
9. The positive electrode active material according to any one of claims 1 to 3, characterized in that The powder resistivity R of the positive electrode active material is less than or equal to 11Ω•cm.
10. The positive electrode active material according to any one of claims 1 to 3, characterized in that The positive electrode sheet prepared from the positive electrode active material has a compacted density of 2.5 g / cm 3 .
11. A lithium ion secondary battery, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 10.
12. The lithium ion secondary battery according to claim 11, characterized in that: The invention comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector and comprising the positive electrode active material. When the positive electrode sheet and a lithium metal sheet are combined into a button battery, in a 0.1C charge-discharge curve of the button battery, at 2.5-2.9Vvs Li + There are charging and discharging platforms within the voltage range.
13. A battery module, characterized in that: A lithium ion secondary battery comprising the lithium ion secondary battery according to claim 11 or 12.
14. A battery pack, characterized in that: The invention comprises at least one of the lithium ion secondary battery according to claim 11 or 12 or the battery module according to claim 13.
15. An electrical device, characterized in that: It comprises one or more of the lithium ion secondary battery of claim 11 or 12, the battery module of claim 13 or the battery pack of claim 14, and the lithium ion secondary battery, the battery module or the battery pack is used as a power source for the electrical device or an energy storage unit for the electrical device.
Citation Information
Patent Citations
Spherical LiFePO4 / (C+La2 / 3-xLi3xTiO3) composite anode material and preparation method thereof
CN103400962A
Composite cladded lithium ion cathode material, and preparation method thereof
CN108206276A